PTH-052 Vitamin D and other micronutrient status in patients with inflammatory bowel disease. (23rd September 2015) - Raychaudhuri, C; Al-Joudeh, A; Srinivas, M; Ellis, R; Bardhan, K D; Willemse, P J; Basumani, P; Höroldt, B
Abstract : Introduction: Low vitamin D has been reported in patients with Crohns Disease (CD). Vitamin D deficiency is associated with no-specific symptoms, has an impact on bone health. Vitamin D may also have chemoproctective and immunomodulatory effects. We assessed the Vitamin D and other micronutrient status of patients attending the IBD clinic at Rotherham. Methods: 183 patients with IBD (75 Ulcerative colitis (UC), 105 CD); 80 male, 4 Asian, median age 46 (17–89) years. Patients on vitamin supplements were excluded. Measurements: vitamin D, calcium profile, CRP, FBC available for all; vitamin B12, folate, ferritin/iron studies available in 158 patients. Frequencies were compared by Fisher exact test. Patients on calcium and vitamin D or other vitamin supplements and those on medication interfering with vitamin D metabolism were excluded. Vitamin D (25HOD) categories: deficient, <25 nmol/l; insufficient, 25–50 nmol/l; adequate, >50 nmol/l. Results: (a) 51.9% (96 patients) had suboptimal vitamin D levels (36 deficient; 60 insufficient). (b) Deficiency of vitamin D, vitamin B12, folate were common in CD than UC (22 vs 14%, 24 vs 13%; 6 vs 1%), but iron deficiency was not (12 vs 11%); none of these significant. (c) Median vitamin D levels were higher in autumn than spring, but neither deficiency nor insufficiency were significantly more common (CD p=0.25; UC p=0.51; Fischer exact test). (d) Median level were higher in men than women, but not significantly (CD p=1.0, UC p=0.70). (e) Vitamin D deficiency/insufficiency was significantly more common in patients >60 years in CD but not UC (p=0.003; UC p=0.10). (F) Vitamin D deficiency/insufficiency was more common in active disease in Crohn's but not UC, this bordered significance (p=0.05 and p=1.0). (g) No patient had a vitamin D level in the toxic range. Conclusion: Suboptimal vitamin D levels are present in over 50% of patients attending our IBD clinic; deficiency in almost 20%; seasonal variation while present does not explain the high prevalence. Other micronutrient deficiencies are also frequently present. We advocate annual "vitamin check" (vitamin D, B12, folate and ferritin) for IBD patients similar to the one frequently performed for patients with coeliac disease.